Analisis Manajemen Risiko Operasional pada Coffeeshop: Pendekatan Identifikasi, Evaluasi, dan Pengendalian Risiko - Tansa Bihisma Sinatrya; Amirah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The rapid expansion of the coffee shop industry has exposed business owners to various risks, ranging from supply chain disruptions and inconsistent ingredient quality to shifting customer behaviors. This study aims to capture how these risks arise and how effectively coffee shops are able to mitigate them. Data were collected through questionnaires distributed to individuals directly involved in day-to-day operations, ensuring that the findings reflect real conditions rather than assumptions. A descriptive quantitative approach was used to identify patterns of risk based on the respondents’ actual working experiences. Initial results indicate that many coffee shops still face significant vulnerabilities, particularly in terms of fluctuating ingredient prices, irregular stock availability, and operational issues such as inconsistent beverage quality or service errors. Additional risks stem from intense market competition and technological problems, including interruptions in digital payment systems. Although several establishments have begun adopting certain control measures, their risk identification and assessment processes remain incomplete. These findings emphasize the necessity for a more structured risk management framework to help coffee shops adapt, survive, and compete within a constantly evolving industry landscape.